2023
DOI: 10.1038/s41420-023-01420-2
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 mediated PARylation contributes to myogenic progression and glucocorticoid transcriptional response

Abstract: The ADP-ribosyltransferase, PARP1 enzymatically generates and applies the post-translational modification, ADP-Ribose (ADPR). PARP1 roles in genome maintenance are well described, but recent work highlights roles in many fundamental processes including cellular identity and energy homeostasis. Herein, we show in both mouse and human skeletal muscle cells that PARP1-mediated PARylation is a regulator of the myogenic program and the muscle transcriptional response to steroid hormones. Chemical PARP1 modulation i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Thus, the fate of muscle (whether it is formed or wasted) may depend on the specific PARP which is expressed and active under these conditions. We, as well as others, have shown that the expression of PARP1 decreases upon induction of muscle cell differentiation [ Supplementary Figure S5c, d , ( 63 , 102 , 103 )]. The decreased expression of PARP1 is thought to be a requisite for the induction of the myogenic process and the health of muscle fibers ( 63 , 103 ).…”
Section: Discussionmentioning
confidence: 67%
“…Thus, the fate of muscle (whether it is formed or wasted) may depend on the specific PARP which is expressed and active under these conditions. We, as well as others, have shown that the expression of PARP1 decreases upon induction of muscle cell differentiation [ Supplementary Figure S5c, d , ( 63 , 102 , 103 )]. The decreased expression of PARP1 is thought to be a requisite for the induction of the myogenic process and the health of muscle fibers ( 63 , 103 ).…”
Section: Discussionmentioning
confidence: 67%